Principal Communication Management to Improve Teacher Performance - Herdiana Herdiana; Yusrizal Yusrizal; Khairuddin Khairuddin (STAI Hubbulwathan Duri, 2021)
The purpose of this study is about the communication management of school principals to improve teacher performance at an elementary school Banda Aceh. The research method used is qualitative analysis (non-statistical) according to the aims and objectives of education research. This research is intended to develop the effectiveness of the products used in schools regarding decision making by school principals and to improve teacher performance which is expected to improve the quality of education. The results showed that Principal communication improves teacher professionalism, conveys messages to teachers, and can carry out this information. The principal as a teacher must guide all school members and carry out their duties and functions as school managers in improving the learning process through classroom supervision, fostering, and providing positive suggestions to teachers.